2018
DOI: 10.1017/jfm.2018.93
|View full text |Cite
|
Sign up to set email alerts
|

On a unified breaking onset threshold for gravity waves in deep and intermediate depth water

Abstract: We revisit the classical but as yet unresolved problem of predicting the breaking onset of 2D and 3D irrotational gravity water waves. This study focuses on domains with flat bottom topography and conditions ranging from deep to intermediate depth (depth to wavelength ratio from 1 to 0.2). Our calculations based on a fully nonlinear boundary element model investigated geometric, kinematic and energetic differences between maximally recurrent and marginally breaking waves in focusing wave groups. Maximally stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
149
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(170 citation statements)
references
References 62 publications
20
149
1
Order By: Relevance
“…The third type of criteria is dynamic and is based on the local energy flux velocity recently presented in Barthelemy et al (2018). For two dimensional flows, this breaking criterion can be reduced to a dynamical criterion: Bx = u 1 (xc, t)/C, where C is the (local) crest velocity, xc the position of the crest, and u 1 the horizontal orbital velocity at the crest.…”
Section: Wave Breaking Detection Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The third type of criteria is dynamic and is based on the local energy flux velocity recently presented in Barthelemy et al (2018). For two dimensional flows, this breaking criterion can be reduced to a dynamical criterion: Bx = u 1 (xc, t)/C, where C is the (local) crest velocity, xc the position of the crest, and u 1 the horizontal orbital velocity at the crest.…”
Section: Wave Breaking Detection Criteriamentioning
confidence: 99%
“…Wave breaking is detected when Bx = u 1 (xc, t)/C > σ i . Kurnia and van Groesen (2014) proposed σ i ∈ [0.7, 1], whereas Barthelemy et al (2018) suggest that breaking occurs when Bx is larger than [0.85, 0.86] for waves in deep and intermediate water depths. The same authors expect a similar range of values to be valid for shallow water conditions.…”
Section: Wave Breaking Detection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…On the surface, the expression for normalized energy flux (denoted by symbol B) reduces to the ratio of fluid velocity at the crest to the translational velocity of the crest for the tallest wave in the evolving group. Barthelemy et al (2018) found that a value of Bth=0.85 provides a robust threshold for breaking onset for 2-D wave packets propagating in deep or intermediate uniform water depths. Further targeted study of representative cases of the most severe laterally-focused 3-D wave packets in deep and intermediate depth water shows that the threshold remains robust.…”
Section: Problem Statementmentioning
confidence: 96%
“…This can be primarily attributed to different choices for averaging periods, as discussed in detail in Derakhti et al (2018). Barthelemy et al (2018) showed that highest nonbreaking waves were clearly separated from marginally breaking waves by their normalized energy fluxes localized near the crest tip region, and that initial breaking instability occurs within a very compact region centered on the wave crest. On the surface, the expression for normalized energy flux (denoted by symbol B) reduces to the ratio of fluid velocity at the crest to the translational velocity of the crest for the tallest wave in the evolving group.…”
Section: Problem Statementmentioning
confidence: 99%